Stunting prevention: balanced nutrition education, fill my plate, and complementary food variations for breast milk - Halimatus Sa`diyah; Ainassabih Liwani Syarafina; Dzuhri Ananda Firdaus; Mitra Dwi Murti (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2024)
Optimal nutrition is very important for normal growth and the physical and intellectual development of children. One effort to maintain balanced nutrition is to use a "Fill My Plate" meal portion consisting of fifty percent fruit and vegetables, and the remaining fifty percent consisting of carbohydrates and protein. However, there are still very few mothers who understand how to balance the contents of my plate for the nutritional needs of toddlers. The impact is that the stunting rate in Indonesia is still high. One way to prevent stunting is by educating mothers about the contents of my plate and indicators of nutritional adequacy for toddlers. This community service aims to prevent stunting by increasing knowledge about balanced nutrition, what's on my plate, and variations in complementary foods for breast milk (MP ASI). The mechanism for implementing this activity consists of four activity steps, namely planning, implementation (providing material, questions and answers, pre and post-test questions), activity monitoring, and evaluation. The results of this socialization showed that there was an increase in parents' knowledge of balanced nutrition and variations of MP ASI in the good category with the pretest score which was previously at 51.56%, in the posttest it increased to 74.9% after the education was provided.